Financial Management Model in Realizing the Economic Independence of Islamic Boarding School - Ibadi, Hosnul; Masruroh, Nikmatul; Is’adi, Munir (The Eastasouth Journal of Social Science and Humanities, 2024)
Islamic boarding schools are non-profit organizations. In its development, Islamic boarding schools are not only institutions that only concentrate on tafaqquh fiddin, but also develop businesses in order to realize economic independence, so that Islamic boarding schools do not depend on other institutions or on student contributions. However, the problems faced are, first, how is the financial management pattern applied in order to realize the economic independence of Islamic boarding schools? second, what are the forms of economic independence of Islamic boarding schools that have been realized? This study uses a qualitative approach with a case study type. This study took the object at PP. Manbaul Ulum Wonosari Bondowoso. Data were collected using observation, interview and documentation techniques. Data were analyzed using the flow model stages from Miles and Huberman. The data validity test used triangulation of sources, techniques and time. So that the results obtained, first, that the financial management model of Islamic boarding schools is directly led by the Kiai, the management is handed over to trusted administrators. There is a planning process through budgeting, implementation, supervision and evaluation. The decision maker is the Kiai as the central leader of the Islamic Boarding School. Second, the form of economic independence of Islamic boarding schools is realized through the formation of business units such as banner printing, photocopying business, book store, uniform store, grocery store, santri cooperative, food stall/canteen, stationery store, reception decoration, and Ambarsa Mart. The profit from these businesses is managed for the needs of the Islamic boarding school. So, economically the Islamic boarding school has independence.